Strengthening Community’s Financial Organization Network in Rattaphum District, Songkhla Province - Boonpok, Thitipat; ธรรมสัจการ, วันชัย; Jiaramat, Aim-on (Journal of Liberal Arts Prince of Songkla University, 2023)
This research, entitled “Strengthening Community’s Financial Organization Network in Rattaphum District, Songkhla” aimed to identify the strengths, weaknesses, and opportunities for improving the community economy through the Community's Financial Organization (CFO) in Rattaphum District, Songkhla. The study focused on establishing cooperative networks and implementing best practices in financial management. The research utilized a case study approach and centered on the community financial organization group in Rattaphum District, Songkhla Province. This study comprised three stages of data collection from 156 participants. The results showed that 1) regarding different types of CFOs and their characteristics, village funds operated under formal regulations while production-oriented saving groups and other financial entities in the community adopted more flexible and independent management approaches. However, certain weaknesses were identified, including committees primarily comprising older individuals, a lack of volunteers to lead committees, non-adherence to rules by some members, limited financial resources, and inadequate administrative planning. Nevertheless, all community financial groups had opportunities to enhance the community economy with support from both government and private sectors. 2) Concerning the types of CFO networks, the study identified four categories of CFO networks: district-level networks, sub-district-level networks, networks operating in specific sub-district areas, and some CFOs without any network affiliation. 3) As for good practices in CFO financial management, the research identified seven effective practices in financial management within CFOs. The paper is concluded with recommendations for policy makers and future research.